Addressing Financial Distress in Halal MSMEs: Comparative Evidence from Indonesia and Malaysia - Surya, Intan Febina; M. Djidin; Utami, Pertiwi (Sharia Business Management UIN Raden Intan Lampung, 2025)
This study investigates the challenges of access to financing, internal financial management, and operational issues affecting the financial difficulties of Halal-certified MSMEs in Indonesia. It also examines Malaysian policies as best practices to identify potential policy contributions in the future. The study uses a comparative qualitative approach through in-depth interviews with halal MSMEs, Islamic financial institutions, and policymakers in both countries, supported by an analysis of regulatory documents and the national halal industry development framework. The research results show that financial distress in Indonesia is influenced by the dominance of collateral-based financing schemes, policy fragmentation between halal certification and the Islamic financial system, and weak internal financial governance among business actors. Meanwhile, Malaysia demonstrates a more integrated halal industry ecosystem through a national masterplan and institutional coordination, although managerial capacity constraints remain among micro-enterprises. Theoretically, this research extends Financial Constraint Theory from a sharia economic perspective by emphasizing the importance of institutional integration and a maqashid-based financial architecture in mitigating financial vulnerability. Policy implications emphasize the need to integrate the halal certification system with sharia financing, strengthen profit-sharing-based instruments, and improve literacy and digitalization of halal MSME financial records. Keywords: Access to financing, financial distress, halal MSMEs, sharia economy